Determination of the seasonal heat consumption based on the short-term measurements in the building. (May 2017) - Specjał, Aleksandra; Bartosz, Dorota
The article presents the balance approach of determining the building heat consumption (for heating and ventilation purposes) in the standard heating season based on short-term measurements performed on the real object in actual climatic conditions. The influence of the length of measurements in situ on the accuracy of estimation of the seasonal heat consumption was analysed for the occupied building. The 14-day measurement period was examined as the shortest and it was proved that the accuracy of the heat consumption forecasting was in that case ±20%. The heat consumption for heating and ventilation purposes, determined on the basis of short-term measurements, was recalculated to the reference climatic conditions of the heating season. Such a value is one of the components of the energy performance of a building. According to the Directive of the European Parliament and of the Council on the energy performance of buildings, measurement-based approaches are the alternative for the computational approaches and thus the proposed method can find a practical application in the process of energy certification of buildings. In this article, the results of the application of this method in the multifamily building occupied during the measurements are also presented.